Intratesticular versus intraperitoneal injection of Busulfan for the induction of azoospermia in a rat model - Halimeh Mobarak; Reza Rahbarghazi; Mohammad Nouri; Mohammad Heidarpour; Mahdi Mahdipour (BMC, 2022)
Abstract Background Administration of antineoplastic drugs may cause azoospermia driving to subfertility. Production of animal azoospermia models is essential for evaluating new treatment methods before therapeutic interventions in human setup. This study aimed to investigate the toxic effects of Busulfan (an anticancer drug) on some vital organs and describe the best method and appropriate dose of Busulfan to induce an animal azoospermia model. Methods Rats were randomly assigned into four groups, treatment groups received 10 mg/kg, 40 mg/kg Busulfan intraperitoneally (IP), 5 mg/kg Busulfan intratesticular (IT), and control group. Blood, bone marrow, liver, renal, and testes samples were collected for histological (H&E staining), biochemical (serum levels of ALT, AST, ALP, creatinine, and urea), and hematological analyses. Results Results revealed severe anemia and leukopenia in rats that received Busulfan via IP. By contrast, injection of 5 mg/kg Busulfan via IT did not cause anemia except with a mild decrease in RBC count. Non-significant differences in the M/E ratio were observed in all groups. The administration of 40 mg/kg of Busulfan led to evacuation and destruction in the spermatogenesis process with thin-walled seminiferous epithelium in most tubules, but in rats treated with 10 mg/kg of Busulfan, the normal spermatogenesis process was notified. IT injection of Busulfan contributed to the complete degradation of spermatogenesis in which all spermatogenic cells degenerated. In the renal tissue, hyperemia, extensive tubular necrosis degeneration, and hyaline casts were found after IP injection of Busulfan. In hepatic tissue, focal hemorrhagic, chronic cholangitis, and hepatocyte degeneration, and swelling were noticed. Biochemical analysis revealed apparent Busulfan toxicity of both hepatic and renal tissues in IP Busulfan-treated rats. Conclusions In summary, we found that the intratesticular injection of low doses of Busulfan (5 mg/kg) is a relatively non-invasive and safe method for producing the rat azoospermia model causing the least toxicity on vital organs.